OʻSMIR YOSHDAGI OʻQUVCHILAR KREATIVLIGINI SHAKLLANTIRISHNING PSIXOLOGIK TAHLILI - Djolimbetova, M.M.; Aytmuratova, E.Y. (SCIENCE and SOCIETY, 2024)
In this state, information is presented about the psychological characteristics of pre-adolescence, mental development and independent thinking, creative thinking, intelligence, mainly studying the meaning of creativity in various literature and ix analysis.